Beliefs, Attitudes, and Practices of High School Teachers in Handling Students’ Errors: Implications for Error-Tolerant Mathematics Classrooms - Michael A. Clores; Jemil R. Abay (International Journal on Emerging Mathematics Education, 2022)
Proper handling of students’ errors in mathematics provides teaching and learning opportunities. Anchored in the Professional Error Competence Model developed by Wuttke and Siefried, this study investigated junior high school teachers’ beliefs, attitudes, and practices in handling students’ errors in their Mathematics class. The study employed a descriptive-correlational design and surveyed one hundred three Mathematics teachers from public secondary schools in Camarines Sur. A researcher-made survey questionnaire was used to gather the necessary data. All statistical analyses on the data collected, such as weighted mean, Pearson’s r, and Canonical Correlation Analysis were done using SPSS (version 21). The findings show that respondents frequently employed error detection, correction, and prevention strategies. It also demonstrates that both beliefs and attitudes correlated significantly with respondents’ error-handling practices. The study further reveals that the respondents’ attributes (age, sex, educational attainment, field of specialization, number of years in teaching mathematics, and seminars attended) contribute to their practices, beliefs, and attitudes in error handling. However, it is noted that as respondents grow older and gain more teaching experiences in Mathematics, certain error-handling practices, beliefs, and attitudes appear to diminish. It is therefore recommended that the frequency of error handling activities that facilitate learning should be increased further in a Mathematics class. School administrators should organize training programs that highlight the critical role of error handling in the learning process. They should also embark on benchmarking activities, mentoring, and coaching to expose teachers to error-handling strategies that promote an error-tolerant mathematics classroom where students have numerous opportunities to learn. Moreover, schools should provide students with opportunities to evaluate their teachers’ practices in handling errors. Finally, future researchers should perform actual observations on error handling practices to learn more about them in the classroom setting. They may also look into how teachers deal with errors in online education.